BOOK@HAND BIDL: Mobile Exploring of the Bulgarian Iconography by Using Panorama Pictures - László Márkus, Zsolt; Kaposi, Gábor; Szkaliczki, Tibor; Luchev, Detelin; Pavlov, Radoslav (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2015)
The paper presents the newest developments in integrating Bulgarian Iconographical Digital Library (BIDL) and the tourist mobile application family named as (GUIDE@HAND). The integration made it possible for collections to be created by the user at the BIDL Web page and then downloaded to the GUIDE@HAND Veliko Tarnovo application by using QR codes. This year, a new standalone offline mobile application (BOOK@HAND) was created providing information on icons available in BIDL where the collection presentation functionality of the former system was enhanced with new features. The main novelty of the application is the option to present collections in a virtual exhibition room by using panorama pictures in off-line mode.